Estimating Hedge Ratio and The Hedging Effectiveness of Stock Index Futures Contract - Islam, Mohd Aminul; Mohd Noar, Nor Zaihan (2014)
This study investigates the hedging effectiveness of stock index futures for two Asian markets namely Kuala Lumpur Composite Index futures of Malaysia and Heng Seng stock Index futures of Hong Kong. We employed four different econometric methods such as-conventional ordinary least squares (OLS) model, vector autoregression (VAR) model, error correction model (ECM) and generalized autoregressive conditional heteroskedasticity (GARCH) models to estimate optimal hedge ratio and its hedging effectiveness. We found that ECM model provides better results with respect to risk reduction. In other words, in terms of hedging effectiveness, ECM model exhibits better performance and Hong Kong market appears to provide better hedging performance to market participants compared to Malaysian futures market.